Del individualismo antropotécnico hacia la hospitalidad - Driollet de Vedoya, Teresa (Sapientia, 2019)
In this article, we refer to “the second individualism" characteristic of Postmodernity, described for Gilles Lipovetsky. The sociologist warns that around the 1970s, a total desire for individual freedom, indifference and apathy towards everything that is foreign to us, a search for immediate satisfaction together with an unparalleled desire for seduction and consumerism, took hold of the human being. In this line of exaltation of the individual we find the new eugenic technical ideal. Norbert Wiener and Peter Sloterdijk, among other scientists, had declared that the time had come to produce and modify man himself. The transhumanist thinkers and scientists in this line, armed with great institutional and economic support, work to achieve human genetic eugenics; to keep mortality as far away as possible by regenerative techniques and to create a post-human being. We wonder if this “enhanced man¨ is a realized man. Hospitality seems to have two sides: by giving ourselves as a home for those who are in need, paradoxically, we increase and realize our physical and spiritual capacities, as Romano Guardini, Edmond Jabès, Emmanuel Levinas and Adela Cortina have taught us to discern. We will dwell in particular on some of Nikolai Berdiaev's considerations, who affirms that only in communion or in the cordial reception of the other does the encounter with oneself take place and the contact with the mystery that envelops and escapes all that is human.